KERJA SAMA BILATERAL INDONESIA DAN AUSTRALIA DALAM PENANGANAN TERORISME DI INDONESIA TAHUN 2002 – 2013 - Ansari, Rahmat; Utomo, Tri Cahyo; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The development of terrorism on global scale triggers Indonesia and Australiato increase their capacity by working together to tackle terrorism in Indonesia.In order to determine the actions undertaken by the Government of Indonesiaand Australia to respond and prevent terrorism crime growing in Indonesia,the research use the approach of liberalism, that the relationship betweenIndonesia and Australia based on the same view to protect themselves from thethreat of terrorism through cooperation to increase the capacity of the countryagainst non-state actor, terrorist organizaton. Details about the importance ofcooperation between Indonesia and Australia done within the scope ofcooperation to deal with terrorism in Indonesia focused on government acttoward police institution, Indonesian National Police (Polri) for Governmentof Republic of Indonesia, and Australian Federal Police (AFP) for Governmentof Australia in the area of counter terrorism. Polri and AFP relationship inorder to overcome terrorism crime using curative and preventive action basedon the following bilateral cooperation between states. Counter terrorism actbased on Momerandum of Understanding Between Government of Republic ofIndonesia and Government of Australia signed on 7th February 2002.